Сталинская премия по литературе. Институциональное измерение эстетики социалистического реализма (1940-1950-е годы) - Dmitry Tsyganov (eSamizdat)
The article considers the Stalin Prize for Literature as an institution that had a direct impact on the formation of the socialist realist canon. The study not only contextualizes the institutional cultural history of late Stalinism, but also attempts to discover the inherent stabilising potential of this institution, which ensured the integrity of the cultural continuum of the late Stalinist era through which the profound transformation of mass consciousness was carried out. Using a wide range of factual material, it is shown that in the 1940s and early 1950s the institution of the prize in the minds of Stalinist functionaries also began to be perceived as one of the main instruments for structuring the world political space. Along with the analysis of archival materials of the Committee for the Stalin Prizes in Literature and Arts (Russian State Archive of Literature and Art, f. 2073) and materials of the Committee for the International Stalin Prizes (State Archive of the Russian Federation, f. 9522), we also draw on materials from the fonds of various organisations and bodies, as well as periodicals of those years, published memoirs, diary/memoirs and other materials available to us.